2006
DOI: 10.1177/112067210601600313
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Alterations in PTEN+/–Mice

Abstract: The morphologic and morphometric results suggest that heterozygous PTEN knockout mice had hypertrophic ON without ultrastructural alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…Moreover, the migratory and differentiation capabilities of glial progenitors are perturbed during E13 to E19 in p27 KIP1 null mice, as there were significant increases in QKI-positive; BrdU-positive cells in the subventricular zone compared to wild-type controls [42] . In addition, reduction in MBP staining is observed in p27 KIP1 knockout mice in the optic nerve, consistent with the requirement for p27 KIP1 and PNS myelination [43] . We have previously showed that p27 KIP1 increases after the ectopic expression of QKI-6/7 in oligodendrocytes [8] .…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, the migratory and differentiation capabilities of glial progenitors are perturbed during E13 to E19 in p27 KIP1 null mice, as there were significant increases in QKI-positive; BrdU-positive cells in the subventricular zone compared to wild-type controls [42] . In addition, reduction in MBP staining is observed in p27 KIP1 knockout mice in the optic nerve, consistent with the requirement for p27 KIP1 and PNS myelination [43] . We have previously showed that p27 KIP1 increases after the ectopic expression of QKI-6/7 in oligodendrocytes [8] .…”
Section: Discussionsupporting
confidence: 74%
“…In addition, Pten -/-L7 mutant mice and Pten -/-Nse mutant mice generally exhibited appearances of thickened axonal and dendritic processes [20,25] , which was also observed in the optic nerve of Pten heterozygous mice [26] . Due to the mosaic expression of Cre recombinase, neuronal hypertrophy in these mice was restricted to neurons that showed Pten inactivation, whilst cells that retained expression exhibited normal cell morphologies, which underscores the cell-autonomous manner in which PTEN regulates cell soma size [20,21,24,25] .…”
Section: Loss Of Pten Leads To Neuronal Hypertrophymentioning
confidence: 99%
“…It has been revealed that PTEN plays a key function for DNA repair and viability following DNA-damaging UVB radiation [ 16 ]. In addition, previous report showed that PTEN knockout mice lead to hypertrophic optic nerve [ 17 ]. Furthermore, recent studies have reported that inactivation of PTEN significantly disrupts intercellular adhesion in the RPE, which leads to AMD-like retinal degeneration in mice [ 18 ].…”
Section: Introductionmentioning
confidence: 99%